Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1126/science.1090704
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning the Energetics of Walking and Running: Swinging the Limbs Is Expensive

Abstract: Explaining the energetics of walking and running has been difficult because the distribution of energy use among individual muscles has not been known. We estimated energy use by measuring blood flow to the hindlimb muscles in guinea fowl. Blood flow to skeletal muscles is controlled locally and varies directly with metabolic rate. We estimate that the swing-phase muscles consume 26% of the energy used by the limbs and the stance-phase muscles consume the remaining 74%, independent of speed. Thus, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(243 citation statements)
references
References 28 publications
(28 reference statements)
12
223
2
2
Order By: Relevance
“…In middle to late stance, ‘hamstring’ EMG activity ceases, while that of the FTI continues (Gatesy, 1999b; Marsh et al ., 2004), consistent with slowing knee flexion and initiating knee extension by around 70% stance (Fig. 3a).…”
Section: Discussionsupporting
confidence: 62%
“…In middle to late stance, ‘hamstring’ EMG activity ceases, while that of the FTI continues (Gatesy, 1999b; Marsh et al ., 2004), consistent with slowing knee flexion and initiating knee extension by around 70% stance (Fig. 3a).…”
Section: Discussionsupporting
confidence: 62%
“…FTI, EDL, FCRM) were generally the lowest force producers. Calculated emu muscle forces compared favorably with EMG data collected for guinea fowl Marsh et al 2004), except for some muscles known to be substantial contributors to the swing phase (ITBCR, ITRCR, IFB) in the guinea fowl, in which greater than expected forces were calculated for the emu.…”
Section: Resultsmentioning
confidence: 68%
“…Most of the kinematic differences in the simulations appeared in the swing phase (figure 3), which may seem paradoxical if the metabolic cost of the swing phase is presumed to be minimal. However, recent studies have suggested that the cost of leg swing in locomotion comprises a substantial portion (up to 30%) of the total metabolic cost [21,31,32]. The body is also less mechanically constrained during swing, affording more freedom of motion.…”
Section: Discussionmentioning
confidence: 99%